Inhibition of Thrombin Generation in Plasma by Fibrin Formation (Antithrombin I) - de Bosch, N. B.; Mosesson, M. W.; Ruiz-Sáez, A.; Echenagucia, M.; Rodriguez-Lemoin, A. (Thrombosis and Haemostasis, 2002)
The adsorption of thrombin to fibrin during clotting defines “Antithrombin I” activity. We confirmed that thrombin generation in afibrinogenemic or in Reptilase defibrinated normal plasma was higher than in normal plasma. Repletion of these fibrinogen-deficient plasmas with fibrinogen 1 (‘γA/’γA), whose fibrin has two “low affinity” non-substrate thrombin binding sites, resulted in moderately reduced thrombin generation by 29-37%. Repletion with fibrinogen 2 (‘γ´/’γA), which in addition to low affinity thrombin-binding sites in fibrin, has a “high affinity” non-substrate thrombin binding site in the carboxy-terminal region of its ‘γ´ chain, was even more effective and reduced thrombin generation by 57-67%. Adding peptides that compete for thrombin binding to fibrin [S-Hir53-64 (hirugen) or ‘γ´ 414-427] caused a transient delay in the onset of otherwise robust thrombin generation, indicating that fibrin formation is necessary for full expression of Antithrombin I activity. Considered together, 1) the increased thrombin generation in afibrinogenemic or fibrinogen-depleted normal plasma that is mitigated by fibrinogen replacement; 2) evidence that prothrombin activation is increased in afibrinogenemia and normalized by fibrinogen replacement; 3) the severe thrombophilia that is associated with defective thrombin-binding in dysfibrinogenemias Naples I and New York I, and 4) the association of afibrinogenemia or hypofibrinogenemia with venous or arterial thromboembolism, indicate that Antithrombin I (fibrin) modulates thromboembolic potential by inhibiting thrombin generation in blood.Presented in part at the XVII Congress of the ISTH, Washington, D. C. (1)
Keywords: Fibrinogen; afibrinogenemia; thrombin; antithrombin; hemostasis